A pilot investigation of the Motivation Behaviors Checklist (MBC): An observational rating scale of effort towards testing for baseline sports-concussion assessment. Issue 6 (2nd July 2016) - Rabinowitz, Amanda R.; Merritt, Victoria; Arnett, Peter A.
ABSTRACT: Background : Baseline neuropsychological testing is commonly used in the management of sports-related concussion. However, underperformance due to poor effort could lead to invalid conclusions regarding postconcussion cognitive decline. We designed the Motivation Behaviors Checklist (MBC) as an observational rating scale to assess effort towards baseline neuropsychological testing. Here we present preliminary data in support of its reliability and validity. Method : MBC items were generated based on the consensus of a panel of graduate students, undergraduates, and a clinical neuropsychologist who conduct neuropsychological evaluations for a sports concussion management program. A total of 261 college athletes were administered a standard neuropsychological test battery in addition to the MBC. A subset of evaluations ( n = 101) was videotape and viewed by a second rater. Exploratory factor analysis (EFA) was used to refine the scale, and reliability and validity were evaluated. Results : EFA revealed that the MBC items represent four latent factors—Complaints, Poor Focus, Psychomotor Agitation, and Impulsivity. Reliability analyses demonstrated that the MBC has good inter-rater reliability (intraclass correlation coefficient, ICC = .767) and internal consistency (α = .839). The construct validity of the MBC is supported by large correlations with examiners' ratings of effort (ρ = –.623) and medium-sized relationships with cognitive performance and self-ratings of effort (|ρ| between .263 and .345). Discriminant validity was supported by nonsignificant correlations with measures of depression and postconcussion symptoms (ρ = .056 and .082, respectively). Conclusions : These findings provide preliminary evidence that the MBC could be a useful adjunct to baseline neuropsychological evaluations for sports-concussion management.